Flaky And Woody Fractures In Nickel-Steel Gun Forgings Microstructural Features Of Flaky Steel (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
HENRY TRAPHAGEN, * Toledo, Ohio (written discussion t).-The occurrence of flakes in steel is a perplexing problem, if we consider this condition as a disease rather than a symptom. But if considered as an exaggerated phase of a common disease, flakes will be recognized as old and well-known enemies. I have frequently found flakes in open-hearth steel, converter steel, and even electric steel; and not only in the so-called alloy steels but in dead soft 12-point carbon castings. In fact, I have some twenty flaky test bars that came from a foundry that manufactures converter steel castings. The physical characteristics of such material are striking in their constancy, for the yield point and elastic limit are always high, the elongation is variable, and the reduction of area is nearly always negligible. Soft steels of this kind can easily be bent to an angle of 150° and the only bad symptom is the appearance of incipient cracks on the surface; when the carbon exceeds 30 points, the bending qualities are seriously affected; and when the carbon reaches the neighborhood of 50 points, the bars are generally pulled short. The elongation is peculiar in that it seems to take place along the whole length of the bar, giving a crinkly appearance such as is found in cast brass and monel metal. Of course, this elongation only takes place in the softer varieties of steel. I have stated that flakes in steel represent exaggerated symptoms of a common disease, and that disease is the presence of higher oxides of iron. In every instance that has come to my attention, this condition is coexistent with the presence of oxides in some form. In open-hearth practice when this condition occurs, almost invariably it will be found that the metal has been loaded with ore or that tons of rusty turnings were being melted. In converter practice, one of three conditions is nearly always present: bad cupola practice, the use of oxygenated pig iron, or faulty tuyeres. With the electric furnace, my experience is quite limited, but the few examples of flaky electric steel that have come to my notice were made from a charge of turnings and low-grade light scrap.